ChemInform Abstract: [Et3NH][HSO4]‐Mediated Functionalization of Hippuric Acid: An Unprecedented Approach to 4‐Arylidene‐2‐phenyl‐5(4H)‐oxazolones. Issue 43 (October 2015) - Parveen, Mehtab; Ahmad, Faheem; Malla, Ali Mohammed; Azaz, Shaista; Silva, Manuela Ramos; Silva, P. S. Pereira
Abstract The remarkable feature of this pathway is that the employed ionic liquid eliminates the use of toxic and expensive acetic anhydride.